PENGARUH KESEHATAN BANK TERHADAP PENYALURAN KREDIT PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2014 - NOFITA RAHMI, MULYA (Jurnal Akuntansi AKUNESA, 2016)
The aim of this study was to determine the health of banks towards lending in terms of REC (Risk Profile, Earnings, Capital) or credit risk, Profitability and Capital. Therefore it is necessary to test the REC indicators Loan Loss Provisioning (LLP) to determine the Risk Profile (credit risk), Return on Assets (ROA) to determine Earnings (Profitability) and Capital Adequacy Ratio (CAR) to determine the Capital so that the indicators The affect lending. Based on the research results that Risk Profile (credit risk) as measured by indicators of Loan Loss Provisioning (LLP) positive effect on bank lending, Earnings (Profitability) positive striving towards lending, and Capital (Capital) were measured using Capital Adequacy Ratio (CAR) indicators has no effect on bank lending.